The Effect of Neuraxial Anesthesia on Maternal Cerebral Hemodynamics - Postma, Ineke R.; van Veen, Teelkien R.; Mears, Scott L.; Zeeman, Gerda G.; Haeri, Sina; Belfort, Michael A. (American Journal of Perinatology, 2014)
Objective Neuraxial anesthesia is known to reduce sympathetic tone and mean arterial pressure. Effects on cerebral hemodynamics in pregnancy are not well known. We hypothesize that cerebral hemodynamic parameters will change with respect to baseline following regional analgesia/anesthesia.Study Design We performed maternal transcranial Doppler of the middle cerebral artery in 20 women receiving epidural analgesia for labor, and 18 undergoing spinal anesthesia for cesarean section at baseline, 5 and 15 minutes. Systemic blood pressure (BP), systolic/diastolic/mean velocity, resistance and pulsatility index (PI) were recorded. Cerebral perfusion pressure, critical closing pressure (CrCP), resistance area product, and cerebral flow index were calculated.Results Epidural placement was associated with significant decreases in systolic/diastolic BP/mean velocity/CrCP after 15 minutes, with a corresponding increase in PI. In the spinal group, systolic/diastolic BP/mean velocity uniformly decreased and remained low after 15 minutes, and PI significantly increased and remained constant after 15 minutes. No differences were seen in BP or cerebral hemodynamics between the groups.Conclusion This study demonstrates that both epidural analgesia and spinal anesthesia result in measurable cerebral hemodynamic changes in normotensive term pregnancy that are likely to be clinically insignificant as they do not affect perfusion pressure or flow.
Keywords: neuraxial anesthesia; transcranial Doppler; cerebral hemodynamics; cerebral perfusion pressure